Pengaruh Main Game terhadap Kedisiplinan Anak Remaja di Desa Torbanuaraja - Riski Ankodri Sibarani; Syamsiah Depalina Siregar (PT. Willy Print Art, 2026)
This study examines the influence of gaming activities on adolescent discipline in Torbanuaraja Village through a literature review and contextual analysis. The study focuses on how the intensity of gaming, the type of gaming, and patterns of family and school supervision can contribute to changes in adolescent discipline attitudes, such as tardiness, non-compliance with rules, and decreased academic responsibility. The study incorporates findings from Indonesian studies on gaming addiction, its impact on academic achievement, and changes in social behavior as the basis for the analysis. The analysis shows that without regulation and supervision, the tendency to play games excessively is associated with decreased academic discipline and daily routines in adolescents; conversely, time management and educational interventions can mitigate these negative impacts. This article recommends collaborative strategies between parents, teachers, and community leaders in Torbanuaraja Village to establish healthy gaming patterns and improve adolescent discipline. The conclusion emphasizes the need for local policies and digital literacy programs that are responsive to the village's socio-cultural conditions.